Pengaruh Dewan Direksi, Komite Audit, Coprorate Social Responsibility dan Komisaris Independen Sebagai Variabel Moderasi Terhadap Kinerja Keuangan Perusahaan - Ilham Mukti Prayoga; Andy Dwi Bayu Bawono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to obtain empirical evidence regarding the influence of the board of directors, audit committee, and corporate social responsibility on company financial performance, and to examine whether independent commissioners can moderate these relationships. The object of this research is companies listed in the Jakarta Islamic Index 30 (JII 30) during the 2013–2021 period. The sampling technique used was purposive sampling with a total of 62 company data samples. The data analysis method used multiple linear regression and moderation regression analysis. The results show that the board of directors has a significant influence on financial performance, while the audit committee and corporate social responsibility do not. Independent commissioners are proven to moderate the influence of the board of directors and audit committee on financial performance but are not able to moderate the effect of corporate social responsibility on financial performance.